Inducción para nuevos empleados de POSSIBLE CR - Hoch-Sanabria, Stefani Margarita (Instituto Tecnológico de Costa Rica, 2018)
Everyone, regardless of personality and way of working, take some time to adapt to new processes and spaces. Remember your first day of school, university or work, it sure took you days or months to understand how the organization works, who your colleagues are and where to go in given circumstances. The purpose of this project is to help new employees at Possible, with the first company contact. The work that is presented here has as main objective to understand what those needs are that the new entrants have in order to improve that experience and also decrease this period of “adaptation”. The more accompanied and better informed are the new employees, the company ensures a more natural incorporation in their work environment. Throughout the document, the research relevant to the study of users and their respective needs will be carried out; as well as a design process that respects the validation techniques to ensure that the final result really a response to the problem.
Proyecto de Graduación (Bachillerato en Ingeniería en Diseño Industrial) Instituto Tecnológico de Costa Rica, Escuela de Diseño Industrial, 2018.
Keywords: Outsourcing; Freelancer; Contractor; Full time employee; Research Subject Categories::TECHNOLOGY::Information technology::Computer science::Computer science